An exploratory investigation of glucocorticoids, personality and survival rates in wild and rehabilitated hedgehogs (Erinaceus europaeus) in Denmark - Rasmussen, SL; Kalliokoski, O; Dabelsteen, T; Abelson, K (BioMed Central, 2021)
Background The European population of hedgehogs (Erinaceus europaeus) is declining. It is therefore essential to optimise conservation initiatives such as the rehabilitation of sick, injured and orphaned hedgehogs. Wild animals placed in captivity may be prone to chronic stress, potentially causing negative health effects. Therefore, the effects of these rehabilitation efforts should consequently be evaluated. Furthermore, hand-raising orphaned hedgehogs is a laborious and costly task, and it is therefore relevant to document whether they have equal post release survival rates compared to their wild conspecifics.